Stature Estimation from Femur and Tibia Bone Using Regression Equation Method: A Pilot Study - Mundane , Achal; Awatade , Shraddha; Bhoyar , Lina; Mahakalkar , Archana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Anthropometry plays a crucial role in the field of forensic anthropology, particularly in the identification of human remains. Among the various parameters used for personal identification, stature holds significant importance. It is a key factor in medico-legal investigations, especially when dealing with unknown fragmentary and mutilated remains. The objective of present pilot study was to develop a mathematical formula for estimating human stature based on the measurement of long bones, specifically the femur and tibia. A sample of 150 randomly selected girls, aged between 18 and 24 years, was chosen from Nagpur’s Institute of Forensic Science, Maharashtra. The length of the right tibia and femur bones was measured, calculated and regression formulae was derived to estimate stature for the female population of Maharashtra. To assess the relationship between bone length and stature, Pearson's correlation coefficient was employed and revealed regression coefficient (r) of 0.92 for the femur and 0.77 for the tibia, indicating a significant positive correlation between bone length and stature. Consequently, the findings of this study demonstrate that the length of the femur and tibia bones can serve as reliable predictors for estimating the stature of an individual. In conclusion, anthropometric measurements, particularly those involving long bones such as the femur and tibia, hold immense value in the identification of human remains in the field of forensic anthropology.